Military Medicine in Iraq and Afghanistan A Comprehensive Review. - Greaves, Ian. (Milton : Chapman and Hall/CRC, 2018)
Many, if not most, of the recent improvements in trauma care in civilian practice have developed from military experience. The British Defence Medical Services have been recognised as providers of exemplary health care. Although there willis an emphasis on trauma, this book also captures lessons from internal medicine and infectious disease, ethics (for example dealing with detainees - a particularly controversial subject), human factors, mental health issues and rehabilitation.Military Medicine provides the evidence and context for these innovations, andits unique and important accountwill be ofinterest to both military and civilian practitioners alike.
Operation Herrick phase by phase2003-2006 Return of the Taliban; 2006 Entry into Helmand; Operation Herrick 4 (16 Air Assault Brigade, April to October 2006); Operation Herrick 5 (3 Commando Brigade, October 2006 to April 2007); Sangin -- the town that cost 100 British lives; 2007-2009 The Guerrilla War; Operation Herrick 6 (12 Mechanised Brigade, April to October 2007); Operation Herrick 7 (52 Infantry Brigade, October 2007 to April 2008); Herrick 8 (16 Air Assault Brigade, April to October 2008); Operation Herrick 9 (3 Commando Brigade, October 2008 to April 2009); 2009-2011: Coin
Description based upon print version of record.
Operation Herrick 10 (19 Light Brigade, April to October 2009)
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / History; MEDICAL / Surgery / General; Afghanistan Iraq Conflict; ballistic trauma; Conflict injuries; defence services medicine; disaster medicine; war medicine; Medicine, Military -- Iraq; Medicine, Military -- Afghanistan; Soldiers -- Psychology; Wounds and injuries